A new species of Isoperla Banks (Plecoptera: Perlodidae) from the northeast of the Russian Far East - Teslenko, Valentina A.; Khamenkova, Elena (Zootaxa, 2017)
A new species of Isoperla, I. chereshnevi, is described from the Lankovaya River, Ola River Basin, on the northern coast of the Sea of Okhotsk, northeast of the Russian Far East. The new species description is based on details of the male aedeagus, paraprocts, vesicle, general body coloration, female subgenital plate, and larvae.